2022
DOI: 10.1038/s41598-022-10506-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of crude oil properties impact on wettability alteration during low salinity water flooding using an improved geochemical model

Abstract: In low-salinity water flooding (LSWF), modifying the injected brine composition leads to greater oil recovery from carbonate reservoirs. The processes that control improved recovery during LSWF are not totally clear, which could lead to ambiguities in finding optimum brine composition regarding wettability alteration (WA) toward water wetness. One of the methods to determine WA is bound product sum (BPS) calculation using geochemical tools. In the case of wettability improvement, the BPS value of a crude oil-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In this regard, the tuning parameters in surface complexation of geochemical model are presented in Tables 6 , 7 , 8 for each of the surface sites. The reaction types are validated by Gorbani et al in 2022 35 . Since, the equilibrium constant (Ksp) of calcite is very higher than dolomite (Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the tuning parameters in surface complexation of geochemical model are presented in Tables 6 , 7 , 8 for each of the surface sites. The reaction types are validated by Gorbani et al in 2022 35 . Since, the equilibrium constant (Ksp) of calcite is very higher than dolomite (Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the proposed models are based on the salinity of the brine [50], dissolution of the reservoir rock [9,10,35,51,52], and the concentration of adsorbed specific ion on the rock surface [41,53,54]. Others have used the amount of rock and oil surface species [8,55,56], concentration of adsorbed carboxylic oil component [6,57,58], ionic strength [59], concentration of aqueous ion [60], and migrated fines [61]. Some works have also applied the Deryaguin-Landau-Verwey-Overbeek theory (DLVO theory) to study the wettability alteration mechanism [62][63][64][65].…”
Section: Wettability Alteration Models For Lswfmentioning
confidence: 99%
“…Improvement in wettability for dolomite rock and a negligible effect for calcite rock were observed when temperature increased. It is also stated that the degree of substitution of Mg 2+ with Ca 2+ from the chalk surface increased as the temperature increased . Mahani et al .…”
Section: Introductionmentioning
confidence: 98%
“…It is also stated that the degree of substitution of Mg 2+ with Ca 2+ from the chalk surface increased as the temperature increased. 23 Mahani et al 22 showed that the zeta potential of both rock/brine and oil/brine can reduce toward zero potential as a function of temperature that leads to the positive or negative effect of temperature on wettability alteration depending on the sign of zeta potential of oil/brine and rock/brine. The concentration of the active ions in seawater is much lower than the concentration of non-active ions, Na + and Cl − .…”
Section: Introductionmentioning
confidence: 99%